Pengaruh Brand Ambassador, Brand Image, dan Brand Awareness terhadap Keputusan Pembelian Produk Skincare MS Glow di Kota Surabaya - Sulistyana, Anggraheny; Aminah, Siti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The high market demand in the category of facial skin care series has resulted in various brands emerging and creating intense competition. The purpose of this study was to determine the effect of brand ambassadors, brand image, and brand awareness on purchasing decisions for MS Glow skincare products in the city of Surabaya. MS Glow is a skincare brand that has achieved success with the 2020 Indonesia Best Brand Award (IBBA). The research method used is a quantitative method by distributing questionnaires. The population of this research is MS Glow female consumers who are domiciled in Surabaya, aged at least 17 years, and have purchased MS Glow skincare. The research sample used accidental sampling technique with a total sample of 80 respondents. Data analysis technique using PLS. The results of the study show that brand ambassadors have a significant positive influence on purchasing decisions. Brand Image has a significant positive influence on purchasing decisions. Brand awareness also has a significant positive influence on purchasing decisions. Keywords: Brand ambassador ; Brand Awareness ; Brand Image ; Purchase Decision